An Assessment of MXenes through Scanning Probe Microscopy. Issue 6 (23rd April 2022) - Sahare, Sanjay; Ghoderao, Prachi; Yin, Peng; Saleemi, Awais Siddique; Lee, Shern‐Long; Chan, Yue; Zhang, Han
Abstract: Recently, exploring the unique properties of 2D materials has constituted a new wave of research, which lead these materials to enormous applications ranging from optoelectronics to healthcare systems. Due to the profusion of surface terminated functionalities, MXenes have become an emerging class of 2D materials that can be easily integrated with other materials. The versatility of MXenes allows to tune their finest material properties for further device applications. This review initiates with the classification of preparation methods of MXenes, where the authors elaborate on the significance of top‐down approaches including the exfoliation of solid layers. Next, the focus is diverted toward the materials analysis of MXenes including their terminations analysis as well as their intriguing electrical and mechanical behaviors through scanning probe microscopy. Finally, critical challenges and perspectives for MXenes analysis and applications are explored and discussed. Therefore, this comprehensive review can encourage researchers, and offer a precise direction to employ MXenes in various applications. Abstract : Schematic of MXenes analysis through different kinds of scanning probe microscopy sparks appreciable ideas while encountering the diverse kinds of Mxenes.